2016
DOI: 10.1371/journal.pone.0165393
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neurotrophic Support and Amyloid-Targeted Combined Therapy on Adult Hippocampal Neurogenesis in a Transgenic Model of Alzheimer's Disease

Abstract: Although it is recognized that multi-drug therapies may be necessary to combat AD, there is a paucity of preclinical proof of concept studies. We present a combination treatment paradigm, which temporally affects different aspects of Alzheimer’s disease (AD)-like pathology, specifically Aβ-toxicity and neurogenesis. At early stages of AD-like pathology, in TgCRND8 mice, we found that combating Aβ pathology with scyllo-inositol ameliorated deficits in neurogenesis. Older TgCRND8 mice with established amyloid lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 57 publications
(76 reference statements)
1
9
0
Order By: Relevance
“…To assess neurogenesis proliferation and survival, double immunofluorescent staining and cell counts of EdU co-localized with doublecortin (DCX), and of BrdU co-localized with neuronal nuclei (NeuN) were conducted, respectively (Supplementary material). One in every 10 hippocampal sections were sampled, starting from Bregma −2.28 mm, as previously reported (Morrone et al , 2016). Double staining immunofluorescence of tau with amyloid-β plaques was conducted to demonstrate interaction.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess neurogenesis proliferation and survival, double immunofluorescent staining and cell counts of EdU co-localized with doublecortin (DCX), and of BrdU co-localized with neuronal nuclei (NeuN) were conducted, respectively (Supplementary material). One in every 10 hippocampal sections were sampled, starting from Bregma −2.28 mm, as previously reported (Morrone et al , 2016). Double staining immunofluorescence of tau with amyloid-β plaques was conducted to demonstrate interaction.…”
Section: Methodsmentioning
confidence: 99%
“…For pathological and electrophysiological assessments, we based our sample size on previous experience and published work (McLaurin et al , 2006; Morrone et al , 2016; Bazzigaluppi et al , 2018). In light of up to 20% variation in behavioural readouts, and ensuring power of at least 80% across all contrasts, we thus required 16 rats per group at a significance level of 5% for behavioural analyses to reach statistical significance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, increased proliferation has been observed in the DG from Tg9291 mice aged 9–12 months once amyloid deposition is established (Kolecki et al, 2008). Additionally, recent studies in APP models, harboring both the Swedish and Indiana mutations (Morrone, Thomason, Brown, Aubert, & McLaurin, 2016), have shown that proliferation is also increased in the hippocampus from young mice, and compromised at later stages of the disease. Similarly, hippocampal proliferation and neuronal differentiation increased in young J20 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Further, sI prevents tau hyperphosphorylation (Jin and Selkoe, 2015). These potentially beneficial effects have prompted development of sI and close sI analogs as potential treatments for AD/ADRD (Salloway et al, 2011;Morrone et al, 2016;Lee et al, 2017;Liu et al, 2018). A possible mechanism to explain the low sI signal in supraphysiologic-dose AAS users is that its synthetic enzyme, inositol epimerase, which converts myo-inositol to sI, may be inhibited by AAS.…”
Section: Supraphysiologic-dose Aas Exposures Are Associated With Neurmentioning
confidence: 99%